DISPARITIES CSR IMPLEMENTATION IN DEVELOPING COUNTRIES: CSR PRACTICES IN STATE-OWNED COMPANIES AT THE INDONESIAN STOCK EXCHANGE - Nor Hadi; Khanifah Khanifah; Agus Triyani (AKSES: Jurnal Ekonomi dan Bisnis, 2023)
Corporations have yet to maximally realize their social responsibility in Indonesia. This study seeks to understand companies' reporting of their corporate social responsibility (CSR) programs, as well as investigate the optimal forms and strategies for CRS. Primary and secondary data were collected; the former through interviews with ten corporate actors (CEOs and CSR directors), and the latter through a reading of corporations' annual reports for 2019. Analysis shows that an economic rationale, oriented towards calculating the costs and benefits of programs, is one major reason for CSR falling short of its potential. Further exacerbating the issue, lax government regulations have given corporations significant space in interpreting the best practices. To ensure optimal CSR implementation, an integrated support system may be used, one capable of pressuring corporations through the threat of litigation. Such an integrated support system model would enable government development programs to be integrated with CSR, and to be realized synergistically and sustainably. This article is limited to the perspectives of external stakeholders (governmental, non-governmental, and community actors), and thus further research is necessary to uncover internal perspectives and achieve a more comprehensive understanding.